Standardised inventories of spiders (Arachnida, Araneae) on touristic trails of the native forests of the Azores (Portugal) - Carvalho, Rui (Biodivers Data J, 2021)
BACKGROUND: The sharp increase in tourist visitation of the Azores Archipelago from 2015 onwards raised concerns about the impacts of recreational tourism on native habitats. In response, a project was financed by the Azorean Government to investigate the drivers of biodiversity erosion associated with recreational tourism. Here, we present the data on spider biodiversity found on trails located within the native Azorean forests as they are home to several endemic species of great conservation value. We applied an optimised and standardised sampling protocol (COBRA) in twenty-three plots located in five trails on Terceira and São Miguel Islands and assessed diversity and abundance of spider species at different distances from the trail head and the trail itself. NEW INFORMATION: Of the 45 species (12435 specimens) collected, 13 were endemic to the Azores (9690 specimens), 10 native non-endemic (2047 specimens) and 22 introduced (698 specimens). This database will be the baseline of a long-term monitoring project for the assessment of touristic impacts on native forest trails. This methodology can also be used on other habitats and biogeograhical regions.